Applying VALSAT Analysis and Fishbone Diagram in Lean Manufacturing for Gold Jewelry Production - Wurjaningrum, Febriana; Patricia, Enina (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
This study investigates opportunities to reduce waste in the gold jewelry production process through a qualitative case study approach. Guided by Lean manufacturing principles, value stream mapping was used to visualize the production flow and identify various forms of waste based on the seven wastes framework. Input from production personnel was collected via a closed-ended questionnaire to classify key waste types, while root causes were further explored using value stream analysis tools (VALSAT) and fishbone diagrams. The findings reveal critical inefficiencies in the current process, highlighting areas for targeted improvement. These insights form the basis for proposing actionable strategies to enhance operational efficiency and value creation within the gold jewelry manufacturing industry. While Lean principles are well-established in conventional manufacturing settings, their application to the gold jewelry production process a sector characterized by artisanal craftsmanship and variable workflows remains relatively limited. This study addresses that gap by adapting and applying Lean tools to a traditionally craft-based industry. The integrated methodological approach, which combines Value Stream Mapping, VALSAT, and Fishbone diagrams, strengthens the analysis and supports the development of targeted process improvement proposals. These proposals translate Lean diagnostics into practical, context-specific recommendations for enhancing efficiency in jewelry manufacturing. Abstrak - Studi ini bertujuan untuk mengidentifikasi dan mengusulkan perbaikan untuk mengurangi waste dalam proses produksi perhiasan emas melalui pendekatan studi kasus kualitatif. Dipandu oleh prinsip-prinsip Lean manufacturing, pemetaan aliran nilai digunakan untuk memvisualisasikan aliran produksi dan mengidentifikasi berbagai bentuk pemborosan berdasarkan kerangka kerja tujuh pemborosan. Masukan dari personel produksi dikumpulkan melalui kuesioner tertutup untuk mengklasifikasikan jenis-jenis pemborosan utama, sementara akar penyebabnya dieksplorasi lebih lanjut menggunakan value stream analysis tools (VALSAT) dan fishbone diagrams. Penelitian ini mengungkapkan inefisiensi kritis dalam proses saat ini, menyoroti area untuk perbaikan yang ditargetkan. Wawasan ini membentuk dasar untuk mengusulkan strategi yang dapat ditindaklanjuti untuk meningkatkan efisiensi operasional dan penciptaan nilai dalam industri manufaktur perhiasan emas. Meskipun prinsip-prinsip Lean dalam pengaturan manufaktur konvensional, penerapannya pada proses produksi perhiasan emas, sektor yang dicirikan oleh kerajinan tangan dan alur kerja yang bervariasi, masih relatif terbatas. Studi ini mengatasi kesenjangan tersebut dengan mengadaptasi dan menerapkan alat-alat Lean pada industri yang berbasis kerajinan tradisional. Pendekatan metodologis terpadu, yang menggabungkan value stream mapping, VALSAT, dan fishbone diagrams, memperkuat analisis dan mendukung pengembangan proposal perbaikan proses yang terarah. Penelitian ini menerjemahkan diagnostic Lean menjadi rekomendasi praktis dan spesifik konteks untuk meningkatkan efisiensi dalam manufaktur perhiasan.